MANAGEMENT OF WEIL'S DISEASE WITH SEPSIS AND MULTIPLE ORGAN DYSFUNCTION SYNDROME - S L Sigai, Erlina Ana; Budipratama, Dhany; Ikhwan Nur, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Leptospirosis is a common zoonotic disease with a wide range of clinical manifestations, specifically in tropical regions. Weil's disease is considered a severe form of leptospirosis seen in a minority of leptospirosis cases with considerable mortality. These patients typically developed multiple organ dysfunction (MOD) of acute kidney injury, jaundice, and ARDS. We reported a case of a 62-year-old male transferred to our intensive care unit due to sepsis, severe leptospirosis jaundice, acute respiratory distress, thrombocytopenia, and renal injury. The patient was successfully managed with appropriate antimicrobial treatment and other supportive management, including mechanical ventilation and renal replacement therapy. Moreover, leptospirosis should be considered in any location wherever risk factors are present, not just in epidemic and tropical areas. In this case, we pointed out that serious complications of leptospirosis, such as multiple organ dysfunction, may happen. In such cases, adopting an integrated multidisciplinary team approach is essential to prevent complications and reduce mortality.